Anti Insect Activity of Fruit Extract from Tropical Soda Apple Solanum viarum Dunal Against Aphis gossypii Glover Hemiptera Aphididae - Ramesh, V (International Journal of Pharmaceutical & Biological Archive, 2014)
Anti Insect Activity of Fruit Extract from Tropical Soda Apple Solanum viarum Dunal Against Aphis gossypii Glover Hemiptera Aphididae